background image

4.

a, b

A

: (

f a

f

(

a

b

)

f a

*

f b

)

.

Proof

(1)

(2)

(3)

Due

f a

f

(

a

b

).

(3)

(4)

Obvious.

Remark 7

The definition of straight map can be generalized for any poset

A

by the formula

a, b

A

: (

f a

f b

⇒ ∃

c

A

: (

c

a

c

b

f a

=

f c

))

.

This generalization is not yet researched however.

Proposition 9

Let

f

be a monotone map from a meet-semilattice

A

to some

poset

B

. If

a, b

A

: (

f

(

a

b

) =

f a

f b

)

then

f

is a straight map.

Proof

Let

f a

f b

. Then

f

(

a

b

) =

f a

f b

=

f a

.

Proposition 10

Let

f

be a monotone map from a meet-semilattice

A

to some

poset

B

. If

a, b

A

: (

f a

f b

a

b

)

then

f

is a straight map.

Proof

f a

f b

a

b

a

=

a

b

f a

=

f

(

a

b

).

Theorem 18

If

f

is a straight monotone map from a meet-semilattice

A

then

the following statements are equivalent:

1.

f

is an injection.

2.

a, b

A

: (

f a

f b

a

b

)

.

3.

a, b

A

: (

a

b

f a

f b

)

.

4.

a, b

A

: (

a

b

f a

6

=

f b

)

.

5.

a, b

A

: (

a

b

f a

+

f b

)

.

6.

a, b

A

: (

f a

f b

a

6 ⊃

b

)

.

Proof

15